Pengaruh Kompetensi Negosiasi Tenaga Penjual Terhadap Ketercapaian Target Corporate Contract Hotel: The Influence of Salesperson Negotiation Competence on Hotel Corporate Contract Target Achievement - Farah Munif; Sri Indrayanti; Farah Azahra Haryono (OGZ Research & Publishing, 2025)
This study aims to analyze the influence of salesperson negotiation competence on the achievement of corporate contract targets in hotels. Negotiation competence is considered one of the crucial factors in building sustainable business relationships, particularly with corporate clients who have diverse needs and expectations. The research methodology employed a qualitative approach using in-depth interviews with sales personnel and hotel sales and marketing management. Primary data were collected through a structured set of questions covering aspects such as negotiation preparation, negotiation techniques, relationship-building ability, communication, and strategy adjustment during the negotiation process. The interview results were analyzed descriptively to identify patterns, strategies, and challenges encountered in achieving corporate contract targets. The findings reveal that salesperson negotiation competence plays a significant role in the attainment of corporate contract targets. Thorough preparation through client needs assessment, strategic flexibility in handling objections, and effective two-way communication were found to facilitate agreement achievement. Furthermore, long-term relationships with clients strongly contribute to loyalty and recurring contract opportunities. The main obstacles identified stem from contract requirements perceived as burdensome by some companies; however, these can be mitigated through an adaptive negotiation approach. In conclusion, this study emphasizes that enhancing negotiation competence, particularly in the areas of product knowledge, communication skills, and adaptive strategies, is the key to successfully achieving hotel corporate contract targets.